Development of Project Based Learning Learning Model Assisted by Geogebra Software to Improve Students' Creative Thinking Ability at SMK N 1 Penanggalan - Cibro, Basri; Siregar, Hasratuddin; Rambe, Isnaini Halimah (Journal of Mathematics Technology and Education, 2021)
Mathematics is one of the supporters of the development of science and technology. The low creative thinking of students is one of the causes of students' lack of interest in learning mathematics. The assumption for most students that mathematics is a very heavy and difficult subject, especially in solving Geometry Transformation problems. The purpose of this research is to improve students' creative thinking skills through the development of project-based learning models assisted by geogebra software and the effectiveness of these learning models. This development uses the ADDIE (Analysis, Design, Development, implementation and Evaluation) model. The trial was conducted in class XI TKJ SMK N 1 Penanggalan, Penanggalan District, Subulussalam City, Aceh Province. The results showed that in the first trial there were 12 students who completed with 60% and 8 students did not complete with 40% so that they could not meet the effective criteria. In the second trial there was an increase in creative thinking skills for students who completed as many as 18 students, 85.7% and students who did not complete as many as 3 students, 14.3%. So that the development carried out in the second trial showed an increase in students' creative thinking by 25.7%.